2017
DOI: 10.1159/000458757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Door-Locking Policy on Inpatient Treatment of Substance Use and Dual Disorders

Abstract: Objective: Substance use treatment is often performed inside locked wards. We investigate the effects of adopting a policy of open-door treatment for a substance use treatment and dual diagnosis ward. Methods: This is a prospective open-label study investigating 3-month study periods before opening (P1), immediately after (P2), and 1 year after the first period (P3). Data on committed patients, coercion (seclusion, forced medication, absconding events with subsequent police search), violence, and substance use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…MI was originally developed as a technique for motivating substance abusers to change (Miller and Rollnick, 1991). MI/brief intervention techniques have been proposed as well for the treatment of aggressive behaviour in dual diagnosis (McMurran, 2009;López-Castro et al, 2019), including adolescent (Cunningham et al, 2012;Zatzick et al, 2014), populations albeit conflicting results have been reported (Steinauer et al, 2017).…”
Section: Longer Term Psychological Approachmentioning
confidence: 99%
“…MI was originally developed as a technique for motivating substance abusers to change (Miller and Rollnick, 1991). MI/brief intervention techniques have been proposed as well for the treatment of aggressive behaviour in dual diagnosis (McMurran, 2009;López-Castro et al, 2019), including adolescent (Cunningham et al, 2012;Zatzick et al, 2014), populations albeit conflicting results have been reported (Steinauer et al, 2017).…”
Section: Longer Term Psychological Approachmentioning
confidence: 99%
“…Simpson et al (33) did not report a consistent relationship between substance use and exit security features, intensity of drug/alcohol monitoring and the locking of the ward door. In another study, our research group found no relevant change of substance use on a specialized SUD and dualdiagnosis ward (not the ward under study here) comparing the time period when the ward was closed to the period when the same ward was open (34). As substance use was screened for by urinalysis and breathalyzer testing in the study mentioned above, there may indeed be no increase in substance use after introduction of an open-door policy.…”
Section: Category Quotesmentioning
confidence: 75%
“…The earliest enquiry was published in 1999, investigating the effect of a token economy on patient behaviour . The majority of papers in this theme were written from 2014 onwards, reporting on changed ward practices and their influence on coercive practices (such as open and closed wards); regulations and guidelines for practice; and different service configurations …”
Section: Resultsmentioning
confidence: 99%
“…This may reflect increasing international interest since the mid‐2000s in de‐escalation of violent behaviours by changed ward cultures as first line management strategies . There were a small number of studies which compared coercive practices pre‐post changes in ward policy or management (for instance the effects of change from closed to open wards; whether prioritising enforced medication over seclusion led to a decrease in aggressive incidents and coercive measures; or whether the frequency of seclusion and forced medication altered over 6 years of changing policy) …”
Section: Discussionmentioning
confidence: 99%